1967
DOI: 10.1002/1097-0142(1967)20:1<71::aid-cncr2820200111>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Separation of alkaline phosphatase enzymes in human serum using gel-filtration (Sephadex G-200) techniques

Abstract: With the aid of gel filtration techniques (Sephadex G‐200) the alkaline phosphatase (Bessey‐Lowry‐Brock) distribution patterns have been studied in the serum of control human subjects and of those with conditions known to affect total enzyme levels. Protein was scanned at 254 and 280 mμ and the 19S, 7S, and 4S peaks thus obtained were used as points of reference. The characteristic control serum revealed one sharp peak of enzyme activity in the 7S protein region. A similar but sharper peak was found in osteoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
2

Year Published

1969
1969
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 14 publications
2
6
0
2
Order By: Relevance
“…There are several possible explanations for the existence of isoenzymes, and in this context it is now well established that enzymes may be attached to lipid or lipoprotein components (Moss, 1962;Dunne et al, 1967;Jennings et al, 1970). Such an association has been demonstrated for biliary alkaline phosphatase (Price et al, 1972); in this study of biliary alkaline phosphatase the effect of butanol extraction was to produce another isoenzyme with lower molecular weight and altered electrophoretic mobility, resulting from the removal of a phospholipid moiety from the biliary isoenzyme.…”
Section: Discussionmentioning
confidence: 65%
“…There are several possible explanations for the existence of isoenzymes, and in this context it is now well established that enzymes may be attached to lipid or lipoprotein components (Moss, 1962;Dunne et al, 1967;Jennings et al, 1970). Such an association has been demonstrated for biliary alkaline phosphatase (Price et al, 1972); in this study of biliary alkaline phosphatase the effect of butanol extraction was to produce another isoenzyme with lower molecular weight and altered electrophoretic mobility, resulting from the removal of a phospholipid moiety from the biliary isoenzyme.…”
Section: Discussionmentioning
confidence: 65%
“…Such an association has been demonstrated for alkaline phosphatase (Moss, 1962;Dunne et al, 1967;Jennings et al, 1970;Price and Sammons, 1974). In the case of yGT, it has been suggested that the biliary enzyme may be associated with lipid (Wenham et al, 1978a); furthermore, Beck (1978) suggested that a serum isoenzyme might be associated with a lipid component.…”
Section: Discussionmentioning
confidence: 90%
“…Gel filtration studies were carried out as previously described (Dunne et al, 1967) by eluting 1 ml serum diluted with 2 ml of buffer through a 50 x 21 cm column of dextran gel (Sephadex G 200) containing 1 molar Tris NaCI buffer at pH 8.0. The rate of filtration was controlled by an LKB type 4912A Re-Cychrom infusion 45 pump.…”
Section: Methodsmentioning
confidence: 99%
“…Starch gel studies, while valuable in some hands, have at times produced conflicting results, particularly as regards the origin of normal serum phosphatase. Chiandussi, Greene, and Sherlock (1962) and Kowlessar, Haeffner, and Riley (1961), using starch gel electrophoresis, Dunne, Fennelly, and McGeeney (1967), using gel filtration, and Posen, Neale, and Clubb (1965), using heat inactivation, suggested an osseous origin for control serum enzyme, while Hodson, Latner, and Raine (1962) using similar techniques, and Yong (1967), using agar gel, concluded 'normal serum phosphatase is of hepatic origin'. Immunological studies of Boyer (1963) have shown definite cross reaction between skeletal and hepatic phosphatase, so that method is not suitable for application to clinical work in terms of differential diagnosis.…”
mentioning
confidence: 99%